Malokun Festival and Practices among the Mahin on the Ilaje Coast - Ajishola Omojeje; Raliat Olusola Adu-Peters (Yoruba Studies Review)
Religious beliefs in the precolonial kingdom of Mahin in the Ilaje area of Yorubaland were closely linked to fishing, the fish trade, and other socio-economic activities. Apart from helping to catch fish for immediate consumption, the worship of Malokun facilitated short and long distance trade in fish as a veritable trade article to be exchanged for agricultural goods. This article relies largely on oral interviews gathered from stake-holders such as the practitioners of Malokun religious rites, especially the chiefs and other community members. A group of fishermen were also interviewed alongside some fish sellers in Mahinland and in Igbokoda, the central market of Ilaje. Fishing activity significantly impacted on the development of Mahin in the past. The efficacy of ritual performances is still held in trust by the people whose ways of life are innately fused to the performances of Malokun. The article concludes that like the Mahin, most coastal communities in Yorubaland explored their natural endowments and entrenched them into their socio-economic activities; hence, religious beliefs and economic activities are interwoven and are regarded as inseparable.